Do not plug the TV (Journal of Parents and Teachers, 2014)
Kids and television, a dangerous cocktail. A problem from yesterday but also a current problem. This article offers some guidelines to improve our familiar relationship with this appliance: turning off the t.v., watching t.v. with kids and talks about what they have seen, controlling the time they watch t.v., using t.v. as an educative resource, teaching to watch ads to slow down consumerism, not using t.v. as a babysitter, selecting what we want to watch before turning it on, promoting other activities, not using t.v. as a prize or punishment and leading by example.
Keywords: family and values; television and family; television and education; risks.